Smart cities: the state-of-the-art and governance challenge - Mark Deakin (Triple Helix, 2014)
Reflecting on the governance of smart cities, the state-of-the-art this paper advances offers a critique of recent city ranking and future Internet accounts of their development. Armed with these critical insights, it goes on to explain smart cities in terms of the social networks, cultural attributes and environmental capacities, vis-a-vis, vital ecologies of the intellectual capital, wealth creation and standards of participatory governance regulating their development. The Triple Helix model which the paper advances to explain these performances in turn suggests that cities are smart when the ICTs of future Internet developments successfully embed the networks society needs for them to not only generate intellectual capital, or create wealth, but also cultivate the environmental capacity, ecology and vitality of those spaces which the direct democracy of their participatory governance open up, add value to and construct.
Keywords: 330; Triple Helix; City ranking; Culture; Environment; Future Internet developments; ICTs; Participatory governance and knowledge economy; Regional innovation systems; Smart cities; Social networks